Exceptional boards : environmental experience and positive deviance from institutional norms - Walls, Judith L. (2013)
This paper explores the phenomenon of positive organizational deviance from institutional norms by establishing practices that protect or enhance the natural environment. Seeking to explain why some organizations practice positive environmental deviance while others do not, we locate our inquiry on the board of directors—the organizational body that interprets external issues and guides organizational response. We find a strong correlation between positive deviance and the past environmental experience of board directors and the centrality of the organization within field-level networks. Organizations located on the periphery of the network or whose boards possess a high level of environmental experience are more likely to deviate in positive ways. Our conclusions contribute to multiple literatures in behavioral and environmental governance, the role of filtering and enaction in the process of institutional conformity and change, and the mechanisms behind proactive environmental protection strategies within business.